ANDROID-BASED FINANCIAL STATEMENT PRESENTATION MODEL - Pipit Putri Hariani MD; Indah Purnama Sari; Ismail Hanif Batubara (UIN Sumatera Utara Medan, 2021)
This study aimed to help improve school financial management by diverting the recording of financial data manually and presenting it manually through an android-based financial report presentation model to Muhammadiyah Vocational Schools in Medan City. The android-based financial report presentation model is carried out using descriptive qualitative methods based on the level of effectiveness and efficiency of using tools in the process of analyzing school financial data and supporting government efforts to reduce community activities outside the home, including education workers in order to reduce the spread of the COVID-19 virus as well as in efforts to reduce the spread of the COVID-19 virus in improving the quality of education through the use and use of technology. This research was carried out in several stages, starting from the stage of determining the problem, finding supporting data, and reaching the stage of data analysis; a model was obtained that was able to improve time efficiency in the presentation of financial statements when this model was applied to Muhammadiyah Vocational Schools in particular and other schools in Indonesia. Medan city and other regions, compared to the manual recording and presentation of financial statements.